Introduction to Digital Forensics: Educational Initiatives Through Webinars And Workshops on Recovering Lost Files in the Windows Operating System - Saleh, Oldi Alfani Sunan; Maulana Saputra, Reza Ade; Maulana, Rizky; Haryanda, Muhammad; Mujiastuti, Rully; Sutrisno, Mirza; Hasbi, Muhammad; Adharani, Yana; Rosanti, Nurvelly (Edumedia Solution, 2025)
A webinar and workshop titled